Prevalence of Vitamin B12 Deficiency in Malnourished Children: A Cross-Sectional Study - Madhia Abid; Fehmina Arif (Liaquat National Journal of Primary Care)
The objective of this research paper is to determine the frequency of Vitamin B12 deficiency in malnourished children presenting in outpatient clinics in a Pediatrics Department and to identify associated risk factors using a cross-sectional study design. The research was carried out at the Department of Pediatrics, Dr. Ruth Pfau Civil Hospital Karachi, for 6 months from 22-01-2020 to 21-07-2020. All pediatric patients, aged 6 to 60 months of either gender, either visiting and/or admitted to the Department of Pediatrics, Civil Hospital, were evaluated. Blood samples were obtained from 91 malnourished patients to measure Vitamin B12 levels. Forty-two (46%) children were found to be Vitamin B12 deficient. Children younger than 15 months (19%) and those aged 36 to 60 months (55%) had a high prevalence of Vitamin B12 deficiency. Mean Vitamin B12 levels were136.93±93.23pg/ml. The Regression analysis showed a significant relationship of Vitamin B12 deficiency with socioeconomic status and dominant breastfeeding, (p-value < 0.05). Malnourished children have a higher frequency of vitamin B12 deficiency. Public health initiatives should emphasize balanced feeding practices, combining breastfeeding with adequate complementary foods rich in Vitamin B12.